Does Sharia compliance reflect better environmental, social, and governance (ESG)? Evidence from Indonesia’s energy sector - Awaludin, Azrul Afrillana; Prasetyo, Ari; Yusril, Yusril; Saputra, Deky Chandra (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study aims to compare the environmental, social, and governance (ESG) performance of Sharia-labeled and conventional companies in the energy industry and examine the effect of the Sharia label on ESG performance. This study is important because Sharia-labelled companies are expected to adhere to Islamic values reflected in good corporate governance, demonstrate social responsibility, and participate in environmental conservation. Methodology – This study uses a quantitative approach with a fixed effect model panel data regression technique, involving financial and non-financial data from companies listed on the ISSI and non-ISSI in the 2016-2023 period.Findings – This study found that Sharia companies in the energy sector have lower sustainability (ESG) performance than conventional companies, especially in the environmental dimension. The Islamic dummy variable shows a negative effect on ESG performance, while control variables, such as total assets, DER, and leverage, play an important role in influencing performance. There is no significant difference in social and governance dimensions between Islamic and conventional companies. This study recommends that Islamic stock index screening include sustainability aspects more comprehensively. Implications – Policy makers, industry, and academics can use the findings of this study as recommendations to strengthen sustainable performance in Sharia-labelled companies.Originality – This study analyzes sustainability performance in each industrial sector using materiality-based ESG performance.